Exploring Everyday Nationalism and Methodological Nationalism through Migration Research in Early Childhood and Early Childhood Education ... : Alltäglicher und methodologischer Nationalismus in der Migrationsforschung zu früher Kindheit und frühkindlicher Bildung ... - Imre, Robert; Millei, Zsuzsa (Verlag Barbara Budrich GmbH : Leverkusen, 2022)
Zeitschrift für erziehungswissenschaftliche Migrationsforschung : ZeM 1 (2022) 2, S. 117-133 ... : This paper considers the intersections of migration research in early childhood/education with issues of nationalism. Based on four articles which address migration and inclusion in four Nordic states, first, we demonstrate how migration research can serve as a fertile source for studying everyday nationalism and exploring its operation in teaching and learning settings. Second, applying a critical lens to this type of migration research opens up a reflective space for evaluating the inherent methodological nationalism of some migration research approaches. Our explorations in the article establish the need to rethink the categorizations of migration research in early childhood / education. The set of questioning we develop aid in identifying on the one hand, everyday nationalism and its operation in early childhood / education and on the other hand, methodological nationalism. Without reflexivity on methodological nationalism, migration researchers will keep falling into the trap of reifying everyday ...